Hospice Africa Uganda’s Experience with the Psychosocial and Economic Impact of Caring for Terminally Ill Patients - Nasur Buyinza (Palliative Medicine and Hospice Care, 2024)
Introduction Giving care to a patient at the end-of-life can be a challenging experience. The responsibilities of caregiving may include executing complex physical and mental tasks, financial planning, patient care, decision-making, emotional support and coordination of care. This mixed-methods observational study aims to identify the psychosocial and economic effects of caregiving for terminally-ill patients by carers on the Hospice Africa Uganda Kampala program. It used both quantitative and qualitative data of caregivers caring for terminally-ill patients attending Hospice Africa Uganda Kampala. Simple random sampling was conducted to select caregivers who were invited to participate in the study. Results Results indicate that the majority of patients who were receiving palliative care (60.9%, 103) had been diagnosed with cancer. Most participants (62%, n=105) had spent less than one year caring for their patients, while (18%, n=31) were cared for between 1-5 years. Our results show that the responsibility of caregiving has significant effects on the psychosocial well-being of caretakers. In particular, it reduced the amount of time they spent attending social gatherings and caring for their children, their religious commitment (p<0.05), as well as their level of fatigue and exhaustion (p<0.05), and negatively impacted job finding activities. Conclusion Terminal caregiving has significant effects on the psychosocial well-being and incomes of caretakers, and their ability to find a job alongside caring for the patient. Based on these findings, it is therefore recommended that caregivers be given ongoing sup port to help them provide care to their own family members and patients with life limiting illnesses early in the disease trajectory.